Complement 3 glomerulopathy (C3G) and haemolytic uraemic syndrome (HUS) - Kavanagh, David (Henry Stewart Talks, 2021)
Inherited defects of the complement system in aHUS, Acquired defects of the complement system in aHUS, Cell surface complement dysregulation in aHUS, C3 glomerulopathy (C3G), Murine models of C3G, Clinical disease spectrum